Carbon acquisition ecological strategies to connect soil microbial biodiversity and carbon cycling. (February 2023) - Morrissey, Ember M.; Kane, Jennifer; Tripathi, Binu M.; Rion, Md Shafiul Islam; Hungate, Bruce A.; Franklin, Rima; Walter, Chris; Sulman, Benjamin; Brzostek, Edward
Abstract: Soil carbon feedbacks to global change are uncertain, and the biological processes that govern soil organic matter decomposition are not resolved in current ecosystem models. Though it is recognized that microbial biodiversity influences decomposition rates, incorporating this relationship into ecosystem models is challenging because microbial communities are prohibitively diverse. It is likely necessary to distill microbial biodiversity by focusing on functional groups or ecological strategies. The ecological strategies that currently dominate the microbial ecology literature derive from macroecological theory, have clear weaknesses, and have had limited success when applied to predict soil carbon dynamics. Here, we present a new framework for soil microorganisms: Carbon Acquisition Ecological Strategies (CAES), and we outline a path toward incorporating microbial biodiversity into ecosystem models using this framework to enhance predictions of soil carbon feedbacks to global change. Because a microorganism's diet is central to its ecological niche and likely to covary with other ecologically significant traits, we posit that carbon acquisition may serve as a tractable foundation for developing ecological strategies. We describe four candidate ecological strategies for soil microorganisms: 1° decomposers that assimilate complex plant polymers, 2° decomposers that assimilate microbial necromass, passive consumers that assimilate dissolved organic carbon, and predatory microbes that assimilate live microbial biomass. These strategies are directly linked to soil carbon pools currently represented in ecosystem models and may provide a foundation for greater integration of microbial community dynamics into ecosystem models. Graphical abstract: Image 1 Highlights: Microbes have specialized traits to use distinct pools of soil organic carbon. Carbon acquisition traits may serve as a strong foundation for ecological strategies. Ecological strategies can help condense microbial diversity for inclusion in models.